Proceso de atención de enfermería en paciente de 50 años de edad con insuficiencia renal aguda. - Yánez Chauca, Clara Noemi (2020)
Acute renal failure (IRE) is the sudden deterioration of kidney function over hours or days, generally defined as increase in blood creatinine of 0.5mg/dl/da. In the present clinical case, the situation of a 50 year old patient with acute renal failure after having undergone surgery for the amputation of the big toe of the right foot is described. Thus the relevant signs and symptoms presented by the patient with are abdominal pain, constipation, vomiting and lower limb edema, previous pathology is complicated due to the family history of hypertension and habits that the patient presents, after the evaluation, a nursing care plan has been created to improve the patients quality of life.